2018
DOI: 10.3324/haematol.2018.187708
|View full text |Cite
|
Sign up to set email alerts
|

Setd2 regulates quiescence and differentiation of adult hematopoietic stem cells by restricting RNA polymerase II elongation

Abstract: SET domain containing 2 (Setd2), encoding a histone methyltransferase, is associated with many hematopoietic diseases when mutated. By generating a novel exon 6 conditional knockout mouse model, we describe an essential role of Setd2 in maintaining the adult hematopoietic stem cells. Loss of Setd2 results in leukopenia, anemia, and increased platelets accompanied by hypocellularity, erythroid dysplasia, and mild fibrosis in bone marrow. Setd2 knockout mice show significantly decreased hematopoietic stem and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
40
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 43 publications
1
40
2
Order By: Relevance
“…A growing body of literature has demonstrated that the core transcriptional machinery is not a simple digital switch responding to upstream interactions of transcription factors, but rather a highly regulated, multi-step process that behaves differently within different cells and in different contexts (reviewed by Coulon et al, 3 Goodrich and Tjian, 4 and Jonkers and Lis 5 ). The study by Zhou et al 1 confirms those results in the context of hematopoiesis and stem cell biology, as well as prompts a number of important questions that must now be resolved. Why are erythroid cells more robust to changes in Setd2 activity?…”
supporting
confidence: 67%
See 4 more Smart Citations
“…A growing body of literature has demonstrated that the core transcriptional machinery is not a simple digital switch responding to upstream interactions of transcription factors, but rather a highly regulated, multi-step process that behaves differently within different cells and in different contexts (reviewed by Coulon et al, 3 Goodrich and Tjian, 4 and Jonkers and Lis 5 ). The study by Zhou et al 1 confirms those results in the context of hematopoiesis and stem cell biology, as well as prompts a number of important questions that must now be resolved. Why are erythroid cells more robust to changes in Setd2 activity?…”
supporting
confidence: 67%
“…Prior work integrating Global Run-On sequencing (Gro-Seq) and ChIP-seq of H3K36me3 has demonstrated substantial anticorrelation between this histone mark and polymerase elongation rates. 2 The study by Zhou et al 1 is, to our knowledge, the first to demonstrate in vivo evidence for a directional and putatively causal link of this mark with polymerase kinetics. Moreover, this study provides significant evidence for the importance of Setd2, and consequently H3K36me3, to hematopoietic stem cell function.…”
mentioning
confidence: 94%
See 3 more Smart Citations